One-pot route for uniform anchoring of TiO2 nanoparticles on reduced graphene oxides and their anode performance for lithium-ion batteries - Yoon, Dohyeon; Hwang, Jieun; Kim, Dong Hyun; Chang, Wonyoung; Chung, Kyung Yoon; Kim, Jaehoon (ELSEVIER SCIENCE BV, 2017)
TiO2-reduced graphene oxide (RGO) hybrids were prepared using one-pot, simultaneous reduction of graphene oxide (GO) to RGO and anchoring of TiO2 nanoparticles on the surface of RGO in supercritical isopropanol. Numerous anchor sites facilitating heterogeneous nucleation of TiO2 particles on GO, and extremely fast nucleation due to the supercritical alcohol led ultrafine, well-dispersed anatase TiO2 nanoparticles to anchor to the RGO sheets in a single step. The unique synthetic approach developed herein was very effective for preventing restacking of graphene sheets during reduction, and for tightly anchoring TiO2 nanoparticles to the RGO surface. When the TiO2-RGO with a TiO2 loading of 48 wt% tested as an anode in lithium-ion battery, it exhibited excellent electrochemical performance with a high reversible capacity of 229 mAh g(-1) at 50 mAg(-1) after 50 cycles and a high-rate performance of 115 mAh g(-1) at 1 A g(-1), and 95% of the initial capacity was retained even after 1000 cycles (at rate of 1 A g(-1)). (C) 2017 Elsevier B.V. All rights reserved.
Keywords: SUPERCRITICAL ALCOHOLS; MESOPOROUS ANATASE; CATALYTIC COMBUSTION; ELECTRODE MATERIALS; DIESEL SOOT; LI; INTERCALATION; NANOSHEETS; COMPOSITE; INSERTION